RISK IDENTIFICATION AND ALLOCATION OF BUILDING CONTRUCTION RENOVATION PROJECT IN THE PARTE CLUB SURABAYA BUILDING - Irfan, Bachtiar Muhammad; Witjaksana, Budi (Fakultas Teknik Universitas Tanjungpura, 2023)
The Parte Club Surabaya Building Renovation Project has encountered various problems. These issues arise from multiple factors, primarily due to the complex nature of the structure as it involves renovating an old building. This research aims to identify the dominant risks and allocate the responsibility for managing these risks to the most appropriate party involved. Quantitative research methods were employed for this study. The sample consisted of 18 individuals, including expert staff from the implementing contractor and supervisory consultant. Data collection involved primary data obtained through purposive sampling, with 18 respondents selected. Secondary data included a review of previous similar research literature studies and historical data from earlier projects with similarities. The results of the data processing stage indicated the presence of dominant risks during project implementation and risk allocation. Consequently, project implementation is susceptible to risks identified by analyzing 27 selected risk variables. Six risk variables were dominant in project implementation: construction changes, additional expenses (overheads), project delays, material damage/loss, design errors, and changes to the work schedule. Risk allocation assessment results indicated that 19 risks were allocated to contractors, 3 to owners, and 5 jointly between the owner and contractor (shared). The percentage distribution of risk allocation is as follows: 70% to the contractor, 11% to the owner, and 19% allocated jointly (shared) between the two parties.